The ecological consequences of logging in the burned forests of East Kalimantan, Indonesia - Nieuwstadt, M.G.L. van; Sheil, Douglas; Kartawinata, K. (2001)
Results of a 2-year study on post-fire vegetation dynamics in the unlogged dipterocarp rainforest of Sungai Wain near Balikpapan East Kalimantan, Indonesia are discussed. Results showed that the maintenance of a productive permanent forest estate is likely to be served best by avoiding logging activities in burned areas.